New Molecular Targets of Anticancer Therapy – Current Status and Perspectives - Zajac, Marianna; Muszalska, Izabela; Jelinska, Anna (Current Medicinal Chemistry, 2016)
Molecularly targeted anticancer therapy involves the use of drugs or other substances affecting specific molecular targets that play a part in the development, progression and spread of a given neoplasm. By contrast, the majority of classical chemotherapeutics act on all rapidly proliferating cells, both healthy and cancerous ones. Target anticancer drugs are designed to achieve a particular aim and they usually act cytostatically, not cytotoxically like classical chemotherapeutics. At present, more than 300 biological molecular targets have been identified. The proteins involved in cellular metabolism include (among others) receptor proteins, signal transduction proteins, mRNA thread matrix synthesis proteins participating in neoplastic transformation, cell cycle control proteins, functional and structural proteins. The receptor proteins that are targeted by currently used anticancer drugs comprise the epithelial growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR) and vascular endothelial growth factor receptor(VEGFR). Target anticancer drugs may affect extracellular receptor domains (antibodies) or intracellular receptor domains (tyrosine kinase inhibitors). The blocking of the mRNA thread containing information about the structure of oncogenes (signal transduction proteins) is another molecular target of anticancer drugs. That type of treatment, referred to as antisense therapy, is in clinical trials. When the synthesis of genetic material is disturbed, in most cases the passage to the next cycle phase is blocked. The key proteins responsible for the blockage are cyclines and cycline- dependent kinases (CDK). Clinical trials are focused on natural and synthetic substances capable of blocking various CDKs. The paper discusses the molecular targets and chemical structure of target anticancer drugs that have been approved for and currently applied in antineoplastic therapy together with indications and contraindications for their application.
Keywords: mTOR patway